Minimally Invasive Exposure of the Maxillary Artery at the Anteromedial Infratemporal Fossa. Issue 1 (12th April 2018) - Rodriguez Rubio, Roberto; Kola, Olivia; Tayebi Meybodi, Ali; Tabani, Halima; Feng, Xuequan; Burkhardt, Jan-Karl; Yousef, Sonia; Lawton, Michael T; Benet, Arnau
Abstract: BACKGROUND: The maxillary artery (MA) has been described as a reliable donor for extracranial-intracranial high-flow bypass. Existing techniques to harvest MA require brain retraction and drilling of the middle fossa (with or without a zygomatic osteotomy), carrying the potential risks of venous bleeding, injury to the branches of the maxillary or mandibular nerves, muscular transection, or temporomandibular junction disorders. OBJECTIVE: To describe a novel technique to expose the MA without bony drilling and with minimal impact to surrounding structures. METHODS: A conventional curvilinear incision was performed in 10 cadaveric specimens, prior to elevating the scalp to expose the zygomatic root and lateral orbital rim. The sphenozygomatic suture was followed to the anterolateral edge of the inferior orbital fissure (IOF) to locate and harvest the pterygoid segment of the MA. Topographic anatomy was assessed using surrounding landmarks and 3D Cartesian coordinates to define the surgical area. The number of visible MA branches and their lengths were recorded. RESULTS: The MA was successfully exposed in all specimens. This approach allowed 6 branches of MA to be exposed. The average length of exposure was 23.3 ± 8.3 mm and the average surgical area was 2.8 ± 0.9 cm 2 . The IOF was 11.5 ± 4.2 mm from the MA. CONCLUSION: Our technique provides landmarks to identify the distal pterygoid segment of MA as a donor for extracranial-intracranial bypasses without the need for additional craniectomies. Clear anatomical landmarks, including the sphenozygomatic suture, anterolateral edge of IOF, infraorbital artery, and the pterygomaxillary fissure defined a trajectory to efficiently localize the MA with minimal risk to surrounding structures.